Concerted Antibody and Antigen Discovery by Differential Whole-cell Phage Display Selections and Multi-omic Target Deconvolution. Issue 10 (15th May 2023) - Cyr, Matthew G.; Wilson, Henry D.; Spierling, Anna-Lena; Chang, Jing; Peng, Haiyong; Steinberger, Peter; Rader, Christoph
Graphical abstract: Highlights: There is a need for new cell surface antigens in antibody-based cancer therapy. Target-agnostic Fab-phage library selection and sequencing unveil new antigens. Combining proteomics and transcriptomics robustly facilitates antigen identification. Method provides a streamlined approach to antibody drug and target discovery. Abstract: Monoclonal antibody (mAb)-based biologics are well established treatments of cancer. Antibody discovery campaigns are typically directed at a single target of interest, which inherently limits the possibility of uncovering novel antibody specificities or functionalities. Here, we present a target-unbiased approach for antibody discovery that relies on generating mAbs against native target cell surfaces via phage display. This method combines a previously reported method for improved whole-cell phage display selections with next-generation sequencing analysis to efficiently identify mAbs with the desired target cell reactivity. Applying this method to multiple myeloma cells yielded a panel of >50 mAbs with unique sequences and diverse reactivities. To uncover the identities of the cognate antigens recognized by this panel, representative mAbs from each unique reactivity cluster were used in a multi-omic target deconvolution approach. From this, we identified and validated three cell surface antigens: PTPRG, ICAM1, and CADM1. PTPRG and CADM1 remain largely unstudied in the context of multiple myeloma, which could warrant further investigation into their potential as therapeutic targets. These results highlight the utility of optimized whole-cell phage display selection methods and could motivate further interest in target-unbiased antibody discovery workflows.